Implementasi Nilai Karakter Melalui Kegiatan Karang Taruna Dulur Songolas Di Desa Kasikon Kabupaten Malang - Anwar, Khoirul; Rifqi, Ach. Nizam (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This community service program aims to implement character values through the activities of Karang Taruna Dulur Songolas in Kasikon Village, Malang Regency. The initiative was motivated by the village’s socio-economic limitations and the low educational awareness among youth. The program employed a participatory and collaborative approach, engaging young people actively in various stages of implementation, including leadership training, environmental service, social activities, literacy education, and entrepreneurship. The results show that Karang Taruna serves as a strategic platform for shaping youth character by cultivating values such as religiosity, nationalism, independence, mutual cooperation, and integrity. Beyond individual capacity building, the activities have strengthened social solidarity and a sense of community among residents. Overall, this program demonstrates that community-based character education can be an effective strategy for developing empowered, ethical, and socially responsible youth who contribute to sustainable rural development.